Dampak Konsumsi Pemanis Buatan terhadap Profil Glukosa dan Risiko Diabetes Mellitus: Tinjauan Pustaka - Prameswari, Putu Arya Indira; Darwis, Iswandi; Graharti, Risti (Medula, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia resulting from impaired glucose regulation, and its global prevalence continues to rise substantially. Effective management of DM requires an integrated approach involving pharmacological therapy, lifestyle modification, and appropriate dietary strategies, including carbohydrate regulation, consumption of low–glycemic index foods, and restriction of added sugars. Artificial sweeteners such as aspartame, sucralose, saccharin, and stevia are widely utilized as low-calorie sugar substitutes because they provide sweetness without elevating blood glucose levels. Nevertheless, accumulating evidence indicates that the metabolic effects of artificial sweeteners are heterogeneous and depend on the specific compound as well as the physiological condition of the consumer. Experimental studies have shown that stevia and nano-stevia can reduce hyperglycemia in diabetic rat models, while the Rebaudioside M (Reb M) form of stevia has been reported to enhance insulin sensitivity and attenuate weight gain in obese rats. In contrast, intake of sucralose and acesulfame-K at Acceptable Daily Intake levels has been associated with increased subcutaneous and perirenal adipose tissue accumulation, along with vascular endothelial dysfunction in Wistar rats, suggesting a potential elevation in cardiometabolic risk. Saccharin has similarly been shown to disrupt glucose homeostasis and decrease GLP-1 secretion in animal models, independent of insulin release. Human studies yield more variable outcomes. Most individuals with type 2 diabetes exhibit no significant changes in body weight or glycemic control following artificial sweetener consumption, although more than half report gastrointestinal disturbances such as bloating and diarrhea. These divergent findings underscore that each artificial sweetener possesses a distinct metabolic profile; therefore, their use should be tailored to individual needs, particularly among populations with heightened metabolic vulnerability, including patients with diabetes.